Regioselective Synthesis of Potential Non-Quinonoid Prodrugs of Plasmodione: Antiparasitic Properties Against Two Hemoglobin-Feeding Parasites and Drug Metabolism Studies - Cesar-Rodo, Elena; Dupouy, Baptiste; Häberli, Cécile; Strub, Jean-Marc; Williams, David L.; Mäser, Pascal; Rottmann, Matthias; Keiser, Jennifer; Lanfranchi, Don Antoine; Davioud-Charvet, Elisabeth (Molecules, 2024)
Ψ-1,4-naphthoquinones (Ψ-NQ) are non-quinoid compounds in which aromaticity—found in 1,4-naphthoquinones—is broken by the introduction of an angular methyl at C-4a or -8a. This series was designed to act as prodrugs of 1,4-naphthoquinones in an oxidative environment. Furthermore, from a medicinal chemistry point of view, the loss of planarity of the scaffold might lead to an improved solubility and circumvent the bad reputation of quinones in the pharmaceutical industry. In this work, we illustrated the concept by the synthesis of Ψ -plasmodione regioisomers as prodrugs of the antimalarial plasmodione. The presence of a chiral center introduces a new degree of freedom to be controlled by enantioselectivity and regioselectivity of the cycloaddition in the Diels–Alder reaction. The first strategy that was followed was based on the use of a chiral enantiopure sulfoxide to govern the stereoselective formation of (+)Ψ-NQ or (−)Ψ-NQ, depending on the chirality of the sulfoxide (R or S). New sulfinylquinones were synthesized but were found to be ineffective in undergoing cycloaddition with different dienes under a wide range of conditions (thermal, Lewis acid). The second strategy was based on the use of boronic acid-substituted benzoquinones as auxiliaries to control the regioselectivity. Using this methodology to prepare the (±)Ψ-NQ racemates, promising results (very fast cycloaddition time: ~2 h) were obtained with boronic acid-based quinones 25 and 27 in the presence of 1-methoxy-1,3-butadiene, to generate the 4a- and the 8a-Ψ-plasmodione regioisomers 1 and 2 (synthesized in six steps with a total yield of 10.5% and 4.1%, respectively. As the expected prodrug effect can only be revealed if the molecule undergoes an oxidation of the angular methyl, e.g., in blood-feeding parasites that digest hemoglobin from the host, the antimalarial and the antischistosomal properties of both (±)Ψ-NQ regioisomers were determined in drug assays with Plasmodium falciparum and Schistosoma mansoni. Metabolic studies under quasi-physiological conditions and LC-MS analyses were undertaken to reveal the generation of plasmodione from both the 4a- and the 8a-Ψ-plasmodione regioisomers.